Association of Knowledge Level of the Farmers about Sprinkler System of Irrigation with Independent Variables in the Jhunjhunu District of Rajasthan - Kumar, D.; Roy, A.; Mohanty, A. K. (Indian Journal of Hill Farming, 2016)
Water beings a precious natural resource should be used economically in daily use as well as in irrigating the crops. Over irrigation and under-irrigation both may result in decreasing the yield of crop. Tremendously Proper and economical use of water would be advantageous to the farmers as well as it will help in bringing more land under cultivation. In order to use such a precious natural resource economically, sprinkler irrigation system was evolved about 55 years back. Rajasthan is such a state where water is a limiting resource, rains are uneven, drought is a recurring factor, and topography is undulating. Recently the sprinkler irrigation system is getting momentum in the state. But still the farmers are changed to age old pattern of irrigation which causes huge loss of water. The knowledge and attitude play an important role in adoption of improved practices. Keeping in mind the importance of knowledge and attitude, factors associated with attitude and constraints in its adoption, the present study entitled â€œA study on knowledge and adoption of sprinkler system of irrigation by the farmers in the Jhunjhunu district of Rajasthanâ€ is undertaken with the following specific objectives â€œTo measure the knowledge level of the farmers about sprinkler system of irrigationâ€.